TANTANGAN PEMBELAJARAN ABAD-21: PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWER POINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Lusi Amalida; Leli Halimah (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
21st century learning is learning that prepares the 21st century generation where advances in information and communication technology are developing so fast that it has a major influence on various aspects of life including the teaching and learning process. Today in the implementation of various educational programs, we are faced with various challenges that must be faced by teachers. Teachers must always have the competence of 21st century teachers, so that teachers can prepare everything well through various existing innovations by implementing them in class, especially in responding to various needs in the 21st century. This type of research is qualitative research with a case study type. Based on the initial research conducted, the researcher found the problem that the situation of class VI A students at SDN Haurngombong II who generally studied with direct learning models, especially the lecture method, showed that students were less enthusiastic about receiving lessons and caused boredom when studying in class, so this study aims to find out development of power point-based interactive learning media to improve student learning outcomes in class VI A at SDN Haurngombong II. The results of this study are 1) Development of power point-based interactive learning media to improve class VI A students at SDN Haurngombong II.